2018
DOI: 10.26442/terarkh201890275-78
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological aspects of morbidity in the class of digestive organs in Kazakhstan

Abstract: Aim. To study epidemiological aspects of disease, class of diseases of the digestive system in the region of the relative risk in Kazakhstan. Materials and methods. Studied epidemiological parameters are first identified in the incidence and prevalence of class XI ICD in regions of Kazakhstan with the identification of risk relative to the average national level. In a dysfunctional region Kyzylorda region analyzed the performance of its regions and compared with data from medical examination of the population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Moreover, Sabirov et al demonstrated the effect of chemical pollution to the chromosomal mutagenesis in the region of the Aral Sea [8]. Also, a correlation is found that people from the pre-Aral region have the highest frequency of digestive system diseases in Kazakhstan due to high level of pollutant in the water [9].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Sabirov et al demonstrated the effect of chemical pollution to the chromosomal mutagenesis in the region of the Aral Sea [8]. Also, a correlation is found that people from the pre-Aral region have the highest frequency of digestive system diseases in Kazakhstan due to high level of pollutant in the water [9].…”
Section: Introductionmentioning
confidence: 99%